The hollow cylinder tester for asphalt mixtures :design, implementation and applications : a new approach for the advanced characterization of asphalt mixtures (2017)
"As part of this dissertation, a new laboratory equipment named the Hollow Cylinder Tester for Asphalt Mixtures (HCT-AM) was designed and implemented. This is a novel comprehensive apparatus that was designed and implemented at Universidad de los Andes to characterize these materials. This device incorporates advanced loading application and instrumentation systems to study the response of this material when subjected to the individual or combined effects of axial and torsional loads. Due to the important impact of the environment factors on the mechanical response of these mixtures, this laboratory equipment also counts with a robust environmental conditioning system that permits to investigate climatic-mechanical interactions. This laboratory equipment was used as a tool to investigate the effects of partial saturation within an asphalt mixture on the magnitude of its axial and shear linear viscoelastic properties. Finally, axial strain sweep tests were conducted on the same mixture at different degrees of saturation, with the objective of determining the threshold between its linear elastic response and its non-linear elastic and damage behavior under these different moisture conditions. Overall, the results demonstrate that the HCT-AM is a comprehensive laboratory equipment that provides reliable information about the behavior of asphalt mixtures under different loading schemes and environmental conditions. In the specific case of partial saturation, the results suggest that the presence of moisture within the internal structure of the mixture has a remarkable influence on its mechanical response and performance."--Tomado del Formato de Documento de Grado